Digital literacy and the english language classroom: Analyzing teachers’ readiness and policy gaps - Diah Palupi (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: This paper aims to analyze teachers’ readiness in implementing digital literacy and identify the policy gaps affecting technology integration in language classrooms within the framework of the Merdeka Curriculum. Methods: This study uses the systematic literature review (SLR) method to analyze research and policy documents published between 2020 and 2025. Data were collected from the Scopus, ScienceDirect, and Google Scholar databases using keywords such as ‘digital literacy’, ‘EFL teachers’, and ‘Merdeka Curriculum’. The collected data were analyzed using a six-stage thematic analysis to identify patterns, challenges, and policy implications related to teacher readiness and technology integration. Findings: The findings showed that although most teachers have comprehensive understanding of the Merdeka Curriculum concepts, there is a significant gaps between teachers’ understanding and the real classroom practices. The main factor is limitations on teachers’ training, infrastructure, and resource disparities between urban and rural areas. Furthermore, the national education policy is partially responsive to the actual condition on-the-ground. Conclusion: This study concludes that digital literacy is a fundamental competency, not merely an additional skill, for the successful implementation of the Merdeka Curriculum. Although teachers' theoretical understanding is relatively high, there is a significant gap in classroom practice due to infrastructure disparities and training needs that are more focused on pedagogy. Novelty/Originality of this article: This study contributes to the understanding of how digital literacy can serve as a bridge between national education reform and classroom practice. It also highlights the urgent need for continuous professional training and context-based digital education policy to ensure equitable and sustainable implementation of the Merdeka Curriculum across Indonesia.